Determinants of relationship marketing by women small business owners. (4th July 2017) - Sharafizad, Jalleh; Standing, Craig
Abstract : The purpose of this study is to examine the relationship marketing behavior of women small business owners, and the significance of trusted strong-tie relationships for these business owners related to relationship marketing. The study was driven by the following research questions: 'Do women small business owners engage in relationship marketing? And if so why?' and 'Does women small business owners' preference for strong ties drive their relationship marketing behavior?' Semi-structured interviews were conducted with 28 West Australian women small business owners who were recruited through purposive sampling methods. There were four reasons why participants engaged in relationship marketing: direct and indirect contributions to the business; limited time and resources due to the overwhelming roles these women face in business and at home; women small business owners' preference for strong-tie relationships that are based on trust; and the social dimensions of relationship marketing. This study has limitations that tend to be commonly found in exploratory studies, such as a small sample size which limits the researchers' ability to generalize the findings to the broader women small business owner population. Practical implications of the findings and directions for future research are outlined.